2019
DOI: 10.1108/ijse-11-2016-0338
|View full text |Cite
|
Sign up to set email alerts
|

Public governance quality and tax compliance behavior in developing countries

Abstract: Purpose The purpose of this paper is to explore the relationship between public governance quality and tax compliance behavior in developing countries in terms of what transpires between governments and citizens, leading the later to pay or to abstain from paying tax. The study argues that socioeconomic condition is a mediator in the relationship and explains how and why it is so. Design/methodology/approach This study adopts the conceptual approach and connects the concepts through synthesis of literature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
0
28
0
5
Order By: Relevance
“…In a study of Nigeria, Alabede and Zainal Affrin ( 2011 ) discovered that public governance quality shows a significant positive relationship with tax compliance. However, a recent study also suggested that, in the case of developing countries especially, the relationship between governance quality and tax compliance is mediated by socioeconomic conditions (Umar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Nigeria, Alabede and Zainal Affrin ( 2011 ) discovered that public governance quality shows a significant positive relationship with tax compliance. However, a recent study also suggested that, in the case of developing countries especially, the relationship between governance quality and tax compliance is mediated by socioeconomic conditions (Umar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The link between tax compliance and the provision of public goods can be explained by Tax Moral Mechanism, which states that what affects public tax compliance is reciprocity between the government as a tax collector and the public as a taxpayer (Luttmer & Singhal, 2014). This is also supported by The Fiscal Social Contract Theory which states that taxpayers are bound by contracts to finance the government, while the government is also bound by contracts to guarantee the welfare of the community as taxpayers (Umar, 2018). Furthermore, in Tiebout (1956), when people choose a location to live, at the same time, they are willing to accept all the inherent fiscal consequences such as taxes, user charges, fines, and other obligations.…”
Section: Literature Re View: Tax Compliance and Public Good Provisionmentioning
confidence: 97%
“…The income earned is usually used to fund the provision of local public goods and services such as schools, roads, parks, recreational facilities, sewage disposal, waste management, parking services, civil defense, and community development (Wood & Ong, 2012). Taxpayers have an obligation to pay taxes, while the government has an obligation to make sure that citizens as the taxpayers meet their rights (Umar et al, 2018). This is also supported by Abiola & Asiweh (2012) which states that the government has the responsibility to provide basic infrastructure for its citizens such as hospitals, schools, roads, bridges, airports, railways, and ports.…”
Section: Literature Re View: Tax Compliance and Public Good Provisionmentioning
confidence: 99%
See 1 more Smart Citation
“…TE has been considered a subject of discussion for academic research in developed and developing countries (Nurunnabi, 2018;Richardson, 2016;Umar, Derashid, Ibrahim, & Bidin, 2019;Yamen, Allam, Bani-Mustafa, & Uyar, 2018). Policymakers have not had any specific solution to overcome these challenges.…”
Section: Introductionmentioning
confidence: 99%